Mitigation of Malware Ransomware Virus - Ansori, Aan (Department of Informatics Engineering, 2024)
Abstract— This research aims to explore and analyze ransomware mitigation strategies, a type of malware that encrypts data and demands a ransom. A literature review was used to collect and analyze data from academic journals, industry reports, and technical publications. The analysis of the literature indicates that prevention strategies such as user education, routine data Backups, and software updates are effective in reducing the risk of attacks. Early detection technologies, including intrusion detection systems and behavior analysis, have proven capable of identifying attacks before significant damage occurs. A swift and coordinated response, involving the isolation of infected systems and forensic analysis, can minimize impact and recovery costs. The research concludes that ransomware mitigation requires a holistic approach encompassing prevention, early detection, and rapid response. The combination of these strategies is effective in reducing damage and recovery costs following a ransomware attack.Index Terms—Mitigation, malware, and ransomware.